Percepções das mães com filhos internados em unidade de terapia intensiva neonatal - Rosa Caroline Mata Verçosa; Raíssa Fernanda Evangelista Pires dos Santos; Dayse Alves Cardoso; Ana Kelly Lourenço da Silva (Universidade de Pernambuco, 2021)
Objective: to describe the feelings of mothers regarding their children in the neonatal intensive care unit. Method: qualitative approach study of the descriptive type involving 10 mothers with children in the neonatal intensive care unit. Results: it was perceived that fear, longing, sadness, insecurity and impotence are common feelings of mothers with newborns under the care of the neonatal intensive care unit. Final considerations: the participation of the team in welcoming the family and stimulating their active participation is fundamental in conducting quality care. The presence of the parents is a strongly positive aspect when facing the experience of admission in the neonatal intensive care unit. Newborn and mother care should not be limited to a technical or curative approach, this care needs to be idealized from a multidisciplinary perspective.